The Effects of An Alcohol Beverages Self-Control Program on The Drinking Behaviors of Alcohol Use Disorder Patients in Nakhon Ratchasima Health Promoting Hospitals, Thailand - Tueksungnoen, Patcharaporn; Vuthiarpa, Sararud; Soonthonchaiya, Rangsiman (Journal of The Royal Thai Army Nurses, 2021)
The purpose of this quasi-experimental study was to examine the effects of an alcohol beverage self-control program on the drinking behaviors of alcohol use disorder patients in Nakhon Ratchasima Health Promoting Hospitals in Thailand. The sample was composed of 72 male alcohol use disorder patients aged between 20 and 60 years. Subjects were divided into two groups with thirty-six subjects in each group and they were randomly assigned to either the experimental or control group. The experimental group participated in the alcohol self-control program. It consisted of 8 activities, each taking about 90 minutes per week for 8 consecutive weeks, continuously, while the participants in the control group received the standard program of care for alcohol use disorders in the Health Promoting Hospitals. The alcohol drinking behavior scores were measured using the Alcohol Consumption Assessment (ACA: Thai version) before, between, and after participating in the alcohol self-control program. Descriptive statistics were used to represent the personal information about the participants. The effects of the program were determined using repeated measures ANOVA and t-test. The results showed that the mean scores for alcohol drinking behavior in the experimental group were statistically significantly lower across the three times of evaluation after program completion (F = 37.51, p <.001). Additionally, the mean scores for the experimental group were significantly lower than those of the control group (F = 23.281, p <.001). It is recommended that this alcohol self-control program can reduce or stop alcohol drinking behaviors and can decrease the impacts of excessive alcohol drinking behaviors.